Weaving peace: Exploring the meaning of textiles for Afghan communities - Carozzi, Giulia; Bynner, Claire; Miani, Laura; Horner, Lindsey K; Anusas, Myk (Moray House School of Education, 2024)
This report is the account of a one day workshop aimed at exploring how meanings of textiles could be connected to understandings of peace, with a focus on Afghan communities based in Scotland. The overall objective of the day was to create a safe and dialogical space where participants could identify and explore key themes that could become the focal points of a co-constructed research project.
Keywords: Participatory research